Experiences of workplace violence among nursing personnel. - Shrestha, Durga Laxmi (2011)
ABSTRACT: The study entitled "Experiences of Workplace Violence among Nursing Personnel" was carried out in Rapti Sub-regional hospital, Dang. Qualitative ethnographic research approach was adopted to explore the culture of abused personnel who had experienced workplace violence. A purposive sampling technique was used to select 20 nursing personnel. The qualitative data was generated by using guidelines for (i) Focus group Discussion (FGD), (ii) in- depth interview and (iii) key informant interview. Three FGD were conducted: two groups of staff nurses and one group of ANM, tape recording as well as field note was maintained. In-depth interviews were conducted with 4 nursing personnel who had experienced of workplace violence (WPV), the facial expressions, gesture, tone of voice and emotion experienced by respondents were observed during data collection. Two key informant interviews were carried out among organizational chiefs (medical superintendent) to verify the findings. Collected information was transcribed then translated into English for reporting. The voluminous data was reduced into smaller units by doing content analysis to reveal patterns and identify concepts. Findings revealed that nearly one third of respondents were young between age 20-30 years and more than just half of them (11/20) had less than 10 years work experiences. All participants had experienced some types of abuse in their lifetime and majority of them had experienced verbal abuse in their workplace, where the perpetrators were team i.e. particularly by doctors. The nature of verbal abuse was insult, threatening and scolding in front of patients and visitors. Regarding the place of violence majority of them reported the common place of violence was maternity ward particularly during night duty that was experienced. It was also reported that common cause behind the WPV was due to absence of policy to punish the perpetrators. Among the abused personnel, majority of them reported psychosomatic problems: anorexia, insomnia and depression. The studies revealed that majority of respondents were seeking immediate support from colleagues. In term of preventive measures, majority of respondents reported to give training on self protection, staffs counseling for abused and developing violence prevention policy in the workplace. It was revealed that WPV has contributed adverse effect on physical and emotional health of respondents leading to loss of confidence, absenteeism in work and taking leave/change the job. Based on the identified qualitative information, the four themes were developed: low morale, low responsiveness, lack of unity and hazardous work environment which were responsible for increment of WPV. Therefore there identified themes need to be taken in consideration for the violence prevention policy should be developed in the concerned areas to control and prevent the WPV.